The Use and Utility of Aspiration Thrombectomy in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Wei, D.; Mascitelli, J.R.; Nistal, D.A.; Kellner, C.P.; Fifi, J.T.; Mocco, J.D.; De Leacy, R.A. (American Journal of Neuroradiology, 2017)
BACKGROUND: Thrombectomy trials are often specifically interpreted as evidence for the effectiveness of stent retrievers. The effectiveness of other thrombectomy techniques such as aspiration thrombectomy should be validated through further investigation and review.PURPOSE: To evaluate published treatment times and clinical outcomes in patients treated with aspiration thrombectomy or ADAPT (A Direct Aspiration, First Pass Technique) for acute ischemic stroke.DATA SOURCES: A systematic literature review was performed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. MEDLINE, Scopus, and the Cochrane trial register were searched on November 8, 2016.STUDY SELECTION: Twenty studies (n = 1523 patients) were included in this review and meta-analysis. One of these studies was prospective, and the rest were retrospective.DATA ANALYSIS: Meta-analysis was performed by using a random effects model. Data and publication bias were visualized with forest plots and funnel plots.DATA SYNTHESIS: Five studies investigated aspiration thrombectomy only, and 16 studies investigated ADAPT. Of the 16 studies on ADAPT, the rate of successful recanalization (TICI 2b/3) was 89.3% (95% CI, 85.4%–92.3%). The proportion of patients with good clinical outcome (90-day mRS ≤2) was 52.7% (95% CI, 48.0%–57.4%).LIMITATIONS: Studies on ADAPT were retrospective, and there was heterogeneity between studies for successful recanalization (P < .001) and good clinical outcome (P < .001). There was evidence of publication bias for recanalization rates (P = .01), but not for clinical outcomes (P = .42).CONCLUSIONS: ADAPT and aspiration thrombectomy are effective approaches to thrombectomy, with high recanalization rates and excellent clinical outcomes reported in the literature. Aspiration thrombectomy is a promising neurointervention, but large prospective randomized studies are needed to validate its utility.ADAPTA Direct Aspiration, First Pass Technique